2021
DOI: 10.1093/treephys/tpab083
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-influenced competition between the genders of Salix rehderiana

Abstract: Male and female willow plants show spatial segregation of genders along the environmental gradients. Skewed gender ratio of willows is not only related to altitude, but also to nutrient status and sexual competition, which can affect their growth and defense by altering secondary metabolite production. The relationship between metabolites and nutrients in the two genders of Salix rehderiana was explored in the Gongga Mountain. We found gender ratio was altered with a change in soil nitrogen (N) status; in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Cuttings of S. rehderiana were collected from the Hailuogou Natural Reserve of Mount Gongga (101°30 0 to 102°15 0 E, 29°30 0 to 30°20 0 N) in Sichuan Province, China, in March 2019. The monthly average temperature ranges from À4.3 to 12.0°C, and the mean annual air temperature is 3.8°C (Song et al, 2021). The altitude of the sampling plot (102°01 0 E, 29°35 0 N) was approximately 2600 meters.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuttings of S. rehderiana were collected from the Hailuogou Natural Reserve of Mount Gongga (101°30 0 to 102°15 0 E, 29°30 0 to 30°20 0 N) in Sichuan Province, China, in March 2019. The monthly average temperature ranges from À4.3 to 12.0°C, and the mean annual air temperature is 3.8°C (Song et al, 2021). The altitude of the sampling plot (102°01 0 E, 29°35 0 N) was approximately 2600 meters.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…As dioecious woody plants, some Salix species exhibit sex differences in acclimation to the environment, which leads to biased sex ratios in the population (Delph, 1999; Dudley & Galen, 2007; Jiang et al., 2016; Ueno et al., 2007). In our previous studies, it was found that nutrients influence the competition between the sexes of S. rehderiana and Salix paraplesia , which exhibited sex differences in response to water deficiency and nocturnal warming (Liao et al., 2019; Liao et al., 2020; Song et al., 2021). At the transcriptional and metabolic levels, plants can modulate gene expression and metabolite levels to acclimate to abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%